2008
DOI: 10.1097/hjh.0b013e328301a280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypertension therapy based on eprosartan on systolic arterial blood pressure and cognitive function: primary results of the Observational Study on Cognitive function And Systolic Blood Pressure Reduction open-label study

Abstract: The results of the Observational Study on Cognitive function And Systolic Blood Pressure Reduction are supportive of the proposition that antihypertensive therapy based on drugs that target the renin-angiotensin system is associated with preservation of cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 39 publications
2
51
0
3
Order By: Relevance
“…[16][17][18][19][20][21] In addition, as angiotensin-converting enzyme inhibitors, angiotensin receptor blockers and potassium sparing diuretics have an advantage in preventing CI, activation of the renin-angiotensin system or low potassium concentration has been suggested to be involved in CI through possible contributors to CI pathogenesis, including oxidative stress, inflammation, platelet aggregation and vasoconstriction. [22][23][24][25][26][27][28][29] Aldosterone, a crucial factor downstream of the renin-angiotensinaldosterone system, has also been shown to cause target organ damage independent of its effects on blood pressure and to be a potent cerebrovascular risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21] In addition, as angiotensin-converting enzyme inhibitors, angiotensin receptor blockers and potassium sparing diuretics have an advantage in preventing CI, activation of the renin-angiotensin system or low potassium concentration has been suggested to be involved in CI through possible contributors to CI pathogenesis, including oxidative stress, inflammation, platelet aggregation and vasoconstriction. [22][23][24][25][26][27][28][29] Aldosterone, a crucial factor downstream of the renin-angiotensinaldosterone system, has also been shown to cause target organ damage independent of its effects on blood pressure and to be a potent cerebrovascular risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin may even enhance survival in older humans (Bannister et al 2014). Several of these agents also appear to delay cancers, cognitive decline, cardiac dysfunction, and other agerelated diseases and disabilities in several species, including humans (Chiasson et al 2002;Zeymer et al 2004;Basso et al 2005;Dykens et al 2005;Johnson et al 2005;Crandall et al 2006;Hanon et al 2008;Seibel et al 2008;Libby et al 2009;Anfossi et al 2010;Landman et al 2010;Li et al 2010;Tosca et al 2010;Davies et al 2011;Huang et al 2011;Lamanna et al 2011;Lee et al 2011;Liu et al 2011;Monami et al 2011;Pasternak et al 2011;Majumder et al 2012;Roumie et al 2012;Salani et al 2012;Tseng 2012;Anisimov and Bartke 2013;Goldfine et al 2013;Hong et al 2013;Karnevi et al 2013;Martin-Montalvo et al 2013;Quinn et al 2013;Whittington et al 2013;Kennedy and Pennypacker 2014;Mannick et al 2014;Richardson et al 2014). A pipeline of even more interventions is developing that seem to enhance life span in experimental animals.…”
Section: Are There Translatable Interventions?mentioning
confidence: 99%
“…Importantly, the early cognitive deficit of young hypertensive individuals can be reversed with an appropriate antihypertensive therapy, as suggested by previous findings. 24,[57][58][59] The association between high BP and anxiety is supported by a large number of case-control studies, which compared either psychological symptoms in hypertensive and control subjects, or BP in patients with a variety of psychiatric disorders and controls. 60 When examining anxiety disorder, Vetere et al 61 found a higher prevalence in hypertensive individuals compared with controls.…”
Section: Discussionmentioning
confidence: 95%